Case Study: Ethno-STEM Based Learning to Enhance Critical Thinking Skills in Primary School Students - Putri, Dinda Karunia; Widodo, Wahono (Journal of Innovation and Research in Primary Education, 2025)
Critical thinking is essential for preparing students to face global challenges in the 21st century. The Ethno-STEM based learning that integrates traditional knowledge with modern science offers great potential for improving students' understanding of scientific concepts in a contextual and relevant way. This study aims to examine the application of an Ethno-STEM based learning to improve critical thinking skills in primary school. This study employs a descriptive qualitative approach with a case study design, involving 1 school principal, 10 teachers, and 20 students from Sumberwangi Elementary School in Bojonegoro Regency, Indonesia. Data were collected through interviews, observations, and questionnaires to understand teachers' and students' experiences regarding learning in class and the implementation of Ethno-STEM learning. The results indicate that although teachers recognize the importance of using technology in education, challenges such as lack of facilities, teacher training, and Ethno-STEM application knowledge persist. The study found that learning based on local wisdom enhances students' understanding of science but requires continuous teacher training and the provision of adequate technological resources. The study recommends further integrating technology, local wisdom, and STEM to create more interactive and effective learning, ultimately developing students' critical thinking skills.